Hard evidence on soft skills - James J. Heckman; Tim Kautz (Institute for the Study of Labor (IZA), 2012)
This paper summarizes recent evidence on what achievement tests measure; how achievement tests relate to other measures of cognitive ability like IQ and grades; the important skills that achievement tests miss or mismeasure, and how much these skills matter in life. Achievement tests miss, or perhaps more accurately, do not adequately capture, soft skills - personality traits, goals, motivations, and preferences that are valued in the labor market, in school, and in many other domains. The larger message of this paper is that soft skills predict success in life, that they causally produce that success, and that programs that enhance soft skills have an important place in an effective portfolio of public policies.
urn:nbn:de:101:1-201301214376
Keywords: I20; D01; 330; personality; achievement tests; IQ; cognition; Persönlichkeitspsychologie; Messung; Kognition